Intercalation pseudocapacitance in electrochemical energy storage: recent advances in fundamental understanding and materials development - Liu, Yu; Jiang, San Ping; Shao, Zongping (ELSEVIER, 2020)
Electrochemical energy storage (EES) plays an important role in personal electronics, electrified vehicles, and smart grid. Lithium-ion batteries (LIBs) and supercapacitors (SCs) are two of the most important EES devices that have been widely used in our daily life. The energy density of LIBs is heavily dependent on the electrode capacity, in which the charge storage proceeds mainly in three different mechanisms, that is, alloying, conversion, and intercalation. Conventional LIBs show high energy density, but the rate performance is usually unfavorable. As a comparison, the SCs, which store energy based on electrochemical double layer capacitance (EDLC) or surface Faradaic redox pseudocapacitance, shows outstanding rate performance, but the energy density is still much worse than LIBs. Recently, intercalation pseudocapacitance appears as a new type of EES mechanism which stores energy into the bulk of electrode through a battery-like intercalation process but behaves similar to an electrode of SCs (fast reaction kinetics). Such intercalation pseudocapacitance can effectively narrow the gap between SCs and LIBs in energy density and power density, providing a new opportunity for the development of advanced energy storage system with both high energy density and power density. Up to now, more and more reports about intercalation pseudocapacitive materials have been appeared in literature, however, a systematic analysis of the recent development in intercalation pseudocapacitance is still lack. In this article, we provided an in-time review of the recent progress in the understanding of intercalation pseudocapacitive process and the development of related electrode materials for EES. Importance was paid to the difference between Faradaic surface-redox pseudocapacitance and intercalation pseudocapacitance, as well between battery-like intercalation and pseudocapacitive intercalation. Both cation interaction (Li+ and Na+) and oxygen anion intercalation pseudocapacitance was summarized.